Distinct cachexia profiles in response to human pancreatic tumours in mouse limb and respiratory muscle - Rachel L. Nosacka; Andrea E. Delitto; Dan Delitto; Rohan Patel; Sarah M. Judge; Jose G. Trevino; Andrew R. Judge (Wiley, 2020)
Abstract Background Cancer cachexia is a life‐threatening metabolic syndrome that causes significant loss of skeletal muscle mass and significantly increases mortality in cancer patients. Currently, there is an urgent need for better understanding of the molecular pathophysiology of this disease so that effective therapies can be developed. The majority of pre‐clinical studies evaluating skeletal muscle's response to cancer have focused on one or two pre‐clinical models, and almost all have focused specifically on limb muscles. In the current study, we reveal key differences in the histology and transcriptomic signatures of a limb muscle and a respiratory muscle in orthotopic pancreatic cancer patient‐derived xenograft (PDX) mice. Methods To create four cohorts of PDX mice evaluated in this study, tumours resected from four pancreatic ductal adenocarcinoma patients were portioned and attached to the pancreas of immunodeficient NSG mice. Results Body weight, muscle mass, and fat mass were significantly decreased in each PDX line. Histological assessment of cryosections taken from the tibialis anterior (TA) and diaphragm (DIA) revealed differential effects of tumour burden on their morphology. Subsequent genome‐wide microarray analysis on TA and DIA also revealed key differences between their transcriptomes in response to cancer. Genes up‐regulated in the DIA were enriched for extracellular matrix protein‐encoding genes and genes related to the inflammatory response, while down‐regulated genes were enriched for mitochondria related protein‐encoding genes. Conversely, the TA showed up‐regulation of canonical atrophy‐associated pathways such as ubiquitin‐mediated protein degradation and apoptosis, and down‐regulation of genes encoding extracellular matrix proteins. Conclusions These data suggest that distinct biological processes may account for wasting in different skeletal muscles in response to the same tumour burden. Further investigation into these differences will be critical for the future development of effective clinical strategies to counter cancer cachexia.